The contents of vitamin D and antimicrobial peptides with acute inflammatory bacterial diseases of the bronchopulmonary system in children of early age - Kraynya, H. V.; Крайня, Ганна Вікторівна (My University, 2019)
The purpose: to determine the content of vitamin D and antimicrobial peptides in blood serum with acute inflammatory bacterial diseases of a bronchopulmonary system in children of early age.
Keywords: тези доповідей